+0

# Graphing circles help

+2
217
2
+479

Two circles, one centered at $(-3,2)$ and the other centered at $(0,-1)$, are internally tangent as shown.

If the equation of the smaller circle can be written as $x^2 + y^2 + Dx + Ey + F = 0$, find $D + E + F$.

michaelcai  Jul 24, 2017

#1
+5541
0

radius of big circle  =  distance between  (0, -1)  and  (1, 6)  .

radius of big circle  =  $$\sqrt{(1-0)^2+(6--1)^2}=\sqrt{50}=5\sqrt{2}$$

Draw a line from  (0, -1)  to  (-3, 2) . This is the blue line.

length of blue line  =  $$\sqrt{(-3 - 0)^2+(2--1)^2}=\sqrt{18}=3\sqrt2$$

Then, draw a continuation of that line from (-3, 2) to the point on both circles. This is the red line.

length of red line  =  $$5\sqrt2-3\sqrt2=2\sqrt2$$

We know the center of the small circle, and we know the length of the red line, which is a radius of the small circle. So, we can write the equation of the small circle like this...

(x - -3)2 + (y - 2)2  =  (2√2)2                             Multiply out the parenthesees.

(x + 3)(x + 3) + (y - 2)(y - 2)  =  (2√2)(2√2)

x2 + 6x + 9    +   y2 - 4y + 4  =  8

x2 + 6x + y2 - 4y + 13  =  8

x2 + y2 + 6x - 4y + 5    =  0

And......         6 - 4 + 5  =  7

hectictar  Jul 24, 2017
Sort:

#1
+5541
0

radius of big circle  =  distance between  (0, -1)  and  (1, 6)  .

radius of big circle  =  $$\sqrt{(1-0)^2+(6--1)^2}=\sqrt{50}=5\sqrt{2}$$

Draw a line from  (0, -1)  to  (-3, 2) . This is the blue line.

length of blue line  =  $$\sqrt{(-3 - 0)^2+(2--1)^2}=\sqrt{18}=3\sqrt2$$

Then, draw a continuation of that line from (-3, 2) to the point on both circles. This is the red line.

length of red line  =  $$5\sqrt2-3\sqrt2=2\sqrt2$$

We know the center of the small circle, and we know the length of the red line, which is a radius of the small circle. So, we can write the equation of the small circle like this...

(x - -3)2 + (y - 2)2  =  (2√2)2                             Multiply out the parenthesees.

(x + 3)(x + 3) + (y - 2)(y - 2)  =  (2√2)(2√2)

x2 + 6x + 9    +   y2 - 4y + 4  =  8

x2 + 6x + y2 - 4y + 13  =  8

x2 + y2 + 6x - 4y + 5    =  0

And......         6 - 4 + 5  =  7

hectictar  Jul 24, 2017
#2
+79649
+1

Nice, hectictar....!!!!

CPhill  Jul 25, 2017

### 19 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details